Penerapan Hukum De Moivre Untuk Menentukan Nilai Penyisihan Kontribusi Asuransi Jiwa Dwiguna Dengan Metode Canadian - -, Tarisa Kusumawati; Muhamad Fadli Azim; Havid Risyanto; Dadan, Asep (UIN Sultan Maulana Hasanuddin Banten, 2024)
This research examines the application of De Moivre's Law in determining the value of the contribution allowance for endowment life insurance using the Canadian method. Contribution allowance is very important for life insurance companies to meet claims arising in the current or future period. Insufficient contribution allowance can lead to financial risks, especially when claims submitted exceed predictions. This research aims to develop a contribution allowance calculation model using De Moivre's Law in the Canadian method, compare the results with calculations without using De Moivre's Law, and assess the financial implications for insurance companies. Data was taken from the Indonesian Mortality Table IV and processed using Microsoft Excel. The research results show that the Canadian method without De Moivre's Law produces a greater contribution allowance value in the early years, which provides financial benefits for the company.